Protrusion of Cu-TSV under different strain states - Jinxin Liu; Zhiheng Huang; Paul Conway; Yang Liu (2019)
A phase-field-crystal (PFC) model is used to investigate the protrusion of blind TSVs under different strain states. The direction of loading applied to the TSVs has an effect on the protrusion, which is closely related to the copper grains and their orientations at the TSV edges. A nonlinear relation between protrusion and strain rate has been found, which can be explained by different mechanisms of deformation. A higher strain occurring near the top end of the TSVs leads to a larger protrusion of the bind TSVs.